Pengembangan LKPD Fisika Berbasis Etnosains untuk Meningkatkan Hasil Belajar Kognitif Siswa pada Materi Gelombang Bunyi - Muliani, Muliani; Hasmi Br Lembong; Halimatus Sakdiah; Nuraini Fatmi; Nanda Novita (Indo-MathEdu Intellectuals Journal, 2025)
The purpose of this study was to determine the feasibility of Physics LKPD based on ethnoscience and to determine the increase in students' cognitive learning outcomes after using Physics LKPD based on ethnoscience. This study used the research and development (R&D) method with the ADDIE model. The sample used in this study was 2 classes, namely class XI IPA 1 and class XI IPA 2, totaling 37 students. Data collection techniques using questionnaires, tests, and validation sheet instruments from media experts, material experts, and teacher experts. The results of the study obtained from the results of the material expert validator obtained a percentage score of 87% with the criteria of "very feasible". The results of the media expert validator obtained a percentage score of 81% with the criteria of "very feasible". The results of the teacher expert validator obtained a percentage score of 98% with the criteria of "very feasible". Student responses to LKPD obtained a percentage score of 84% with the criteria of "very interesting". The effectiveness of LKPD based on N-gain is 0.58 with the interpretation that there is an increase in cognitive learning outcomes in the moderate category.